The evaluation of alcohol dependent patients with group attidute scale - Pektaş, Özkan; Mırsal, Hasan; Kalyoncu, Ö. Ayhan; Mırsal, Nursal; Beyazyürek, Mansur (Journal of Dependence, 2001)
Objective: Alcohol dependence is biopsychosocial disorder with relapses and remissions. Group psychotherapy in remission process is as functional to prevent relapses as to acquire a new qualifed standard of life. It is very important to render the continuty for attending the group sessions. The aim of this study is to examine the meaning of continuty, effectiveness and integration of the group by evaluating group attidute scale. That scale was applied to the group memberswho had received inptient treatment program in our clinic.Method: We included 32 patients who received treatment in 1996-1998 and were still sober, into the study. The sociodemographical and clinical properties of patients were established by using a semi structured interview form and the group attidute scale was applied.Results: Of patients 90.6% (n=29) were male and 9.4% (n=3) were females. The average age was 46,3 (sd=8,l). The average time of remission after inpatient treatment were 8 months (max 42 months, min 2 months). Of patients 59.4 % (n=19) attended to the session for twice aweek, 25% (n=8) once a week and 15.6% (n=5) attended rarely. It is noticed that the patients had answered the questions related with attending group sessions as “yes" and the questions related with becoming active in sessions as “no”.Conclusion: These outcomes showed the role of passive factors for interaction of the group members.
Keywords: Alcohol dependence; group attidute; sobriety